Keanekaragaman Hama Dominan pada Tanaman Padi (Oryza sativa L.) Di Langsa Timur, Aceh - Nurjannah; Wahyu Firmana Isnijar; Zakia Hanifah Salwa; Herlina Putri Endah Sari; Jatu Purnamawati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Oryza sativa L. is a rice-producing food commodity plant that has high economic value, because of its function as staple food, source of income and source of nutrition for most of Indonesia's population. The availability of rice must always be guaranteed, but often encounters obstacles, one of which is the presence of pests. The purpose of this study was to determine the diversity and dominant pests species on rice plants in 3 villages, i.e Sukarejo, Alue Pineung and Cinta Raja Village, East Langsa District, Aceh. The method used in this research is descriptive explorative field observation using hand collecting sampling. Data analysis was carried out by describing pests, symptoms of attack and continued by calculating the value of the Shannon-Wiener diversity index. Based on the observations, the result showed 6 species of pests were found on rice which consist of 5 orders and 6 families, they are Leptocorisa acuta, Nezara viridula, Oxya serville, Lonchura leucogastroides and Pomacea caniculata. The diversity index values ​​in 3 villages were 1.41-1.72 with highest diversity index value from Alue Pineung Village. Of the 6 types of species, the dominant pest causing the most damage was Leptocorisa acuta (Walang sangit). This research is expected to be a reference in preventing pest attacks in the Langsa. Keywords: Diversity of pests, dominant pests, rice